(untitled) (Journal of the College of Basic Education, 2022)
The research included five chapters:The first chapter included the introduction of the research and its importance, as the special muscle strength plays a distinctive, effective and essential role in developing offensive skills in the game of basketball, especially scoring, as well as the rest of the physical and motor characteristics in order to obtain the physiological adaptation of the body’s organic systems. And that the basketball game is one of the important group sporting events and competitive activities that give its practitioners experience, physical abilities, skills and educational values ​​based on scientific foundations, which contribute to achieving high achievement, development and winning. Basketball requires special physical preparation; In order to raise the player’s efficiency and ability to play this game. He touched on the importance of research in using the resistance training method to develop special muscle strength and scoring in basketball